Religiusitas Hablumminallah Hablumminannas Terhadap Niat Patuh Calon Wajib Pajak dengan Kepercayaan Fiskus sebagai Moderasi - Dewi Kusuma Wardani; Zahrolina Adnafika Ardhani (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study examines the impact of religiosity from the perspective of vertical (hablumminallah) and horizontal (hablumminannas) relationships on the compliance intentions of prospective taxpayers, by examining the moderating function of the level of trust in the tax authorities. This study uses a quantitative approach with an explanatory design. Data were obtained through an online questionnaire from 501 prospective Muslim taxpayers in Indonesia and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that religiosity from the perspective of hablumminallah hablumminannas has a positive effect on the compliance intentions of prospective taxpayers. In addition, trust in the tax authorities is proven to moderate the relationship between religiosity and compliance intentions of prospective taxpayers in the direction of weakening. These findings enrich the study of behavioral taxation through the integrity of psychological factors (religiosity) and institutional (trust in the tax authorities) in one empirical model. and provide practical implications for tax authorities to increase public trust and strengthen moral values in tax education.